RESPONS KEBIJAKAN PENGASUH PESANTREN TERHADAP PENURUNAN KEMAMPUAN MEMBACA KITAB: STUDI KASUS DI PP ASSUNNIYYAH AL-JAUHARI - Maskur Azka; Titin Nurhidayati; Muhammad Maimun (PT. Sulthan Journal Publisher, 2026)
This study aims to analyze the policy responses of Islamic boarding school administrators to the decline in the reading ability of students at the Assunniyyah al-Jauhari Islamic Boarding School in Kencong, Jember. This research used a qualitative approach with a case study. Data collection techniques included observation, interviews, and documentation. The results indicate a decline in reading ability among some students, characterized by a lack of fluency in reading and understanding of the yellow books. In response to this situation, Islamic boarding school administrators established a policy of habituating reading in teaching and learning activities at the madrasah. Implementation of this policy involved the active involvement of religious teachers (ustadz) in guiding and evaluating students' reading abilities. This policy can be categorized as both an educational response and an innovation in learning methods to improve students' reading literacy.